The effect of lanthanides on color properties of the (Bi2O3)0.7(Ln2O3)0.3 compounds - Šulcová P.; Proklešková E. (Journal of Mining and Metallurgy. Section B: Metallurgy)
(Bi2O3)0.7(Ln2O3)0,3 solid solutions were synthesized as new inorganic yellow and orange pigments and their color properties have been investigated as possible ecological materials. The pigments were prepared by the solid state reaction of mixed oxides (Bi2O3)0.7(Ln2O3)0.3 of various rare earth cations (Ln = Eu, Gd, Tm, Yb and Lu). All the synthesized pigment samples were found to have color coordinates, low a* and high b* and exhibit the color from pale light yellow to orange. Reflectance spectra of the samples show high reflectance percentage in the 600 - 700 nm range. Characterization of the (Bi2O3)0.7(Ln2O3)0,3 solid solutions suggests that they have a potential to be alternative yellow colorants for paints, inks, plastics, and ceramics.